Efektivitas Ekstrak Daun Gedi Terhadap Bakteri Penyebab Keputihan Secara In Vitro - Rahmadanu, Risna Ayu; Ardiningtyas, Lisa; Sasmita, Anggun; Wulansari, Meinita (Jurnal Ners, 2025)
Pathological leukorrhea is a reproductive health issue in women caused by fungal infections, one of which is Candida albicans. If it persists, it can affect the fertility function of the reproductive organs, particularly the fallopian tubes. Green Gedi leaves (Abelmoschus manihot L.) are a food plant that contains certain chemical compounds, including steroids, flavonoids, and tannins, which have antifungal effects. This research aims the effectiveness of Gedi leaf extract in inhibiting the growth of Candida albicans. This study employed the diffusion method (direct sensitivity), using extraction through maceration with 96% ethanol and evaporating it using a rotary evaporator at a temperature of 50-60°C. Subsequently, the activity of the Gedi leaf extract against C. albicans was tested, and incubated for 3x24 hours to observe the inhibition zones. The results show there was no inhibitory effect of the Gedi leaf ethanol extract against C. albicans compared to the inhibition zone of the positive control ketoconazole against Candida albicans. Factors affecting the absence of inhibition by the Gedi leaf ethanol extract include the temperature of the growing environment for Gedi leaves, which influences the production of secondary metabolites, and virulence factors of C. albicans pathogenesis. Keywords: greed gedi leaves, Candida Albicans Fungus, Leukorrhea, Reproduction.